Experimental study of the out-of-plane behaviour of masonry infill walls with and without previous in-plane damage - André Furtado (2016)
Recent earthquakes demonstrated a significant contribution of the masonry infill walls in the structural response of the existent reinforced concrete buildings. When subjected to seismic actions, they tend to interact with the surrounding RC frames, which can result in different failure modes depending on the combination of the in-plane and the out-of-plane behaviour. From the surveys on damaged and collapsed RC buildings in the LAquila (Italy) and Lorca (Spain) earthquakes a large number of buildings that suffered severe damage or collapse had their poor performance associated with the influence of the infill panels. The masonry infill walls are considered non-structural elements but, their contribution should be considered in the structural response analysis of existing buildings, for which the understanding out-ofplane non-linear behaviour of infill walls is of full importance in order to develop efficient strengthening solutions to prevent and improve their performance in future earthquakes, and consequently reduce their seismic vulnerability. The main objective of the present paper was to obtain further knowledge concerning to the out-of-plane response of masonry infill walls panels. For this an experimental testing campaign on full scale infill walls was carried out in three experimental (cyclic and monotonic) out-of-plane tests with and without previous in-plane damage. The experimental campaign, material characterization and the test setup will be described along the manuscript as well as the main experimental tests results will be presented and discussed. © 2016 Taylor & Francis Group, London.